Analisis Komitmen (Affective, Continuance dan Normative) Terhadap Kualitas Pelayanan Pengesahan STNK Kendaraan Bermotor (Studi Empiris pada Kantor Bersama Samsat di Propinsi Kalimantan Timur) (Jurnal Manajemen dan Kewirausahaan, 2010)
Adopting an internal marketing approach, this study attempts to provide a deeper understanding of the organisational commitment – service quality relationship in the service context. This is done by empirically testing the relationships that the three components of organizational commitment (affective, continuance and normative) have with the service quality of customer-contact employees. The hypotheses were framed by critically reviewing the extant literature in the areas of services marketing and human resource management. A large sample comparative study was conducted on employees in Kantor Bersama Samsat Di Propinsi Kaltim. Study explore the important question of how the three components of organizational commitment influence the employee-perceived service quality differently in Kantor Bersama Samsat. The findings indicate that in Kantor Bersama Samsat, both affective commitment and continuance commitment have significant positive impact on service quality while in Kantor Bersama Samsat, only affective commitment is found to affect service quality significantly. Having established the commitment–service quality relationship, the implications for designing internal marketing strategies are further discussed.